A preparation method of W-Cu functional gradient material and corresponding material
Through powder extrusion printing technology, the gradient distribution of W and Cu components is controlled, and the problems of low efficiency and high cost of preparation of W-Cu functional gradient materials in the prior art are solved, and efficient and low-cost material preparation is achieved, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202310303003.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-03-27
AI Technical Summary
The prior art is difficult to efficiently prepare W-Cu functional gradient materials, and traditional powder metallurgy methods require subsequent processing. SLM technology has high requirements for raw materials and is low in efficiency and high cost, making it difficult to use for large-scale production.
The W-Cu functional gradient material was prepared by powder extrusion printing. Through the refining, printing, degreasing and sintering processes, the gradient distribution of W and Cu components was controlled to prepare materials with high thermal conductivity and obvious layered gradients.
It improves the processing efficiency and quality of W-Cu functional gradient materials, reduces production costs, and realizes the preparation of materials of different shapes and sizes, which is suitable for large-scale production.
Smart Images

Figure CN116275090B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional gradient materials, and in particular to a preparation method of a W-Cu functional gradient material and corresponding materials. Background Art
[0002] The composition of W-Cu functionally graded materials (FGM) is distributed in a gradient along the cross section. It has the function of thermal stress relief and can give full play to the intrinsic characteristics of each component in the functionally graded material. It has good comprehensive physical and mechanical properties and is widely used in sealing materials and heat sink materials of high-power semiconductor devices.
[0003] Since W has an extremely high melting point and poor wettability with Cu, researchers usually use powder metallurgy to prepare W-Cu functional gradient materials. However, W-Cu functional gradient materials made by traditional powder metallurgy need to be further processed to have a shape and size that meets practical applications. The high hardness and high strength of W-Cu functional gradient materials bring great difficulty to the processing process, and also cause material loss during the processing.
[0004] Additive manufacturing has become a new way to prepare W-Cu functional gradient materials. The Chinese patent with publication number CN114734056A discloses a method for preparing tungsten-copper continuous gradient materials based on SLM technology. However, the SLM technology used in this patent has high requirements for the particle size distribution and shape of the raw material powder, which increases the production cost and difficulty. When preparing materials, SLM technology needs to be sintered layer by layer by laser. This feature makes the preparation of high-melting-point W not only inefficient, but also there may be performance differences in different regions. Therefore, the quality and efficiency of W-Cu functional gradient materials prepared by SLM technology are low, the cost is high, and it is difficult to use for large-scale production.
[0005] Powder extrusion printing (PEP) is a process of extruding the printing feed through a hot melt extrusion system and printing parts of the required shape and size by controlling the movement of the nozzle. This printing technology has the advantages of low requirements for raw material powder, wide application range, low production cost and high preparation efficiency. Lu Tengxuan (Lu Tengxuan, Meng Xiaoyan, Li Shidi, Deng Xin. Additive manufacturing process and microstructure in cemented carbide powder extrusion printing [J]. Materials Engineering, 2022, 50(05): 147-155.) prepared WC-13Co cemented carbide by PEP. The experimental results show that the cemented carbide print parts are almost completely dense, with uniform grain size and high hardness. However, since there is no forming mold and extrusion pressure in the preparation process of PEP technology, it has extremely high requirements for the composition of the adhesive and the subsequent degreasing and sintering processes; at the same time, the samples prepared by PEP still have the problem of low density, so the existing PEP technology cannot realize the printing preparation of W-Cu functional gradient materials.
[0006] Therefore, how to provide a preparation method of W-Cu functional gradient material and improve the processing efficiency and quality of W-Cu functional gradient material has become a technical problem to be solved urgently. Summary of the invention
[0007] In view of this, in order to overcome the deficiencies of the prior art, the present invention provides a method for preparing a W-Cu functional gradient material and corresponding materials.
[0008] In one aspect, the present invention provides a method for preparing a W-Cu functional gradient material, comprising:
[0009] Step 1: W Print Feed Preparation
[0010] The W powder and the wax-based adhesive were mixed at different loading amounts and then kneaded at 180°C for 2 hours, cooled naturally, and the cooled material was crushed and sieved to obtain W printing feed;
[0011] Step 2: W green body preparation
[0012] Add W printing feeds with different loading amounts into the 3D printer in order from large to small loading amounts, and print out W green bodies with a loading amount gradient;
[0013] Step 3: W skeleton preparation
[0014] The W green body prepared in step 2 is subjected to solvent degreasing treatment and thermal degreasing treatment to obtain a degreasing green body, and the degreasing green body is pre-sintered to obtain a W skeleton with a pore gradient;
[0015] Step 4: Preparation of W-Cu functional gradient materials
[0016] The W skeleton prepared in step 3 is subjected to a Cu infiltration treatment to obtain a W-Cu functional gradient material having W and Cu content varying along the cross section.
[0017] Preferably, in the method for preparing the W-Cu functional gradient material of the present invention, in step 1, the particle size of the W powder is 0.2 μm-20 μm.
[0018] Preferably, in the method for preparing the W-Cu functional gradient material of the present invention, in step 1, the wax-based adhesive is composed of 55 vol.% paraffin, 25 vol.% polyethylene, 17 vol.% polypropylene and 3 vol.% stearic acid.
[0019] Preferably, in the method for preparing the W-Cu functional gradient material of the present invention, in step 2, the loading amount of W in the printing feed is 20-60%, and the loading gradient is 2-5 layers.
[0020] Preferably, in the preparation method of the W-Cu functional gradient material of the present invention, in step 2, the printing parameters are printing temperature 150-200°C, substrate temperature 70-100°C, extrusion volume 100-150%
[0021] Preferably, in the method for preparing the W-Cu functional gradient material of the present invention, in step three, the solvent for solvent degreasing treatment is n-heptane or trichloroethylene, the temperature for solvent degreasing treatment is 20-80° C., and the time for solvent degreasing is 12-36 hours.
[0022] Preferably, in the method for preparing the W—Cu functional gradient material of the present invention, in step three, the temperature of the thermal degreasing treatment is 500-900° C., the time of the thermal degreasing treatment is 6-12 hours, and the environment of the thermal degreasing treatment is a hydrogen atmosphere.
[0023] Preferably, in the method for preparing the W—Cu functional gradient material of the present invention, in step three, the pre-sintering temperature is 1400-1700° C., and the sintering time is 30-180 min.
[0024] Preferably, in the method for preparing the W-Cu functional gradient material of the present invention, in step 4, the temperature of the infiltration of Cu is 1100-1500° C., and the time of the infiltration of Cu is 60-300 min.
[0025] On the other hand, the present invention provides a W-Cu functional gradient material, wherein the W-Cu functional gradient material is prepared according to the preparation method of the W-Cu functional gradient material.
[0026] The preparation method of the W-Cu functional gradient material and the corresponding material of the present invention have the following beneficial effects:
[0027] 1. The present invention adopts a powder extrusion printing method to prepare W-Cu functional gradient materials, which not only avoids the problem of difficult subsequent processing of traditional powder metallurgy methods, but also avoids the problems of high requirements for raw materials and low preparation efficiency of 3D printing methods such as SLM.
[0028] 2. The mixing, printing, degreasing and sintering processes of the method of the present invention are stable and controllable, and the prepared W-Cu functional gradient material has high thermal conductivity, obvious layered gradient, and good bonding between the layers.
[0029] 3. The method of the present invention has simple process, high preparation efficiency, low cost, can prepare W-Cu functional gradient materials of different shapes and sizes, is suitable for large-scale production, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 The present invention is a process flow chart of the preparation method of the W-Cu functional gradient material.
[0032] Figure 2 Schematic diagram of the structure of the W skeleton prepared according to the method for preparing the W-Cu functional gradient material of the present invention.
[0033] Figure 3 This is a scanning electron microscope image of a W—Cu functional gradient material prepared according to exemplary embodiment 3 of the present invention.
[0034] Figure 4 This is an EDS image of the W—Cu functional gradient material prepared according to exemplary embodiment 3 of the present invention. DETAILED DESCRIPTION
[0035] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0036] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.
[0037] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.
[0038] Figure 1 The process flow chart of the preparation method of the W-Cu functional gradient material of the present invention; Figure 2 Based on Figure 1 The schematic diagram of the structure of the W skeleton prepared by the method shown in FIG. 1 is a schematic diagram of the structure of the W skeleton prepared by the method shown in FIG. 1 . After removing the binder from the printed body containing the loading gradient and pre-sintering, the following can be obtained: Figure 2 The W skeleton with porosity gradient shown in FIG. Figure 1 The process flow chart shown in the figure provides a detailed description of the preparation method of the W-Cu functional gradient material of the present invention.
[0039] Example 1
[0040] Step 1: W Print Feed Preparation
[0041] W powder with a particle size of 0.2 μm and a wax-based adhesive (composed of 55 vol.% paraffin, 25 vol.% polyethylene, 17 vol.% polypropylene and 3 vol.% stearic acid) were mixed at a W loading of 30% and 20% respectively, and then kneaded at 180° C. for 2 h, cooled naturally, and the cooled material was crushed and sieved to obtain W printing feed;
[0042] Step 2: W green body preparation
[0043] W printing feeds with different loading amounts were added into the 3D printer in descending order, and the printing parameters were printing temperature of 150°C, substrate temperature of 70°C, extrusion amount of 100%, and W green bodies with two layers of loading gradients (30%, 20%) were printed;
[0044] Step 3: Preparation of W skeleton
[0045] The W green body prepared in step 2 is subjected to solvent degreasing treatment with trichloroethylene at 20°C for 24 hours, and then subjected to thermal degreasing treatment in a hydrogen atmosphere at 900°C for 6 hours to obtain a degreased green body, and the degreased green body is pre-sintered at 1400°C for 30 minutes to obtain a W skeleton with a void gradient;
[0046] Step 4: Preparation of W-Cu functional gradient materials
[0047] The W skeleton prepared in step 3 is subjected to a Cu infiltration treatment at 1100° C. for 300 min to obtain a W-Cu functional gradient material having W and Cu content varying along the cross section.
[0048] Example 2
[0049] Step 1: W Print Feed Preparation
[0050] W powder with a particle size of 10 μm was mixed with a wax-based adhesive (composed of 55 vol.% paraffin, 25 vol.% polyethylene, 17 vol.% polypropylene and 3 vol.% stearic acid) at a W loading of 60%, 50%, 40% and 30%, respectively, and then kneaded at 180° C. for 2 h, cooled naturally, and the cooled material was crushed and sieved to obtain W printing feed;
[0051] Step 2: W green body preparation
[0052] W printing feeds with different loading amounts were added into the 3D printer in descending order, and the printing parameters were printing temperature of 200°C, substrate temperature of 100°C, extrusion rate of 150%, and W green sheets with 4 layers of loading gradients (60%, 50%, 40%, 30%) were printed;
[0053] Step 3: W skeleton preparation
[0054] The W green body prepared in step 2 is subjected to solvent degreasing treatment at 80°C for 12 hours using trichloroethylene, and then subjected to thermal degreasing treatment in a hydrogen atmosphere at 500°C for 12 hours to obtain a degreased green body, which is pre-sintered at 1700°C for 30 minutes to obtain a W skeleton with a void gradient;
[0055] Step 4: Preparation of W-Cu functional gradient materials
[0056] The W skeleton prepared in step 3 is subjected to a Cu infiltration treatment at 1500° C. for 60 min to obtain a W-Cu functional gradient material having varying contents of W and Cu along the cross section.
[0057] Example 3
[0058] Step 1: W Print Feed Preparation
[0059] W powder with a particle size of 2 μm was mixed with a wax-based adhesive (composed of 55 vol.% paraffin, 25 vol.% polyethylene, 17 vol.% polypropylene and 3 vol.% stearic acid) at W loadings of 55%, 50%, 45%, 40% and 35%, respectively, and then kneaded at 180° C. for 2 h, cooled naturally, and the cooled material was crushed and sieved to obtain W printing feed;
[0060] Step 2: W green body preparation
[0061] W printing feeds with different loading amounts were added into the 3D printer in descending order, and the printing parameters were printing temperature of 180°C, substrate temperature of 90°C, extrusion rate of 125%, and W green bodies with 5 layers of loading gradient (55%, 50%, 45%, 40%, 35%) were printed;
[0062] Step 3: W skeleton preparation
[0063] The W green body prepared in step 2 is subjected to solvent degreasing treatment at 45°C for 24 hours using n-heptane, and then subjected to thermal degreasing treatment in a hydrogen atmosphere at 800°C for 8 hours to obtain a degreased green body, which is pre-sintered at 1400°C for 60 minutes to obtain a W skeleton with a void gradient;
[0064] Step 4: Preparation of W-Cu functional gradient materials
[0065] The W skeleton prepared in step 3 is subjected to a Cu infiltration treatment at 1350° C. for 120 min to obtain a W-Cu functional gradient material having W and Cu content varying along the cross section.
[0066] Example 4
[0067] Step 1: W Print Feed Preparation
[0068] W powder with a particle size of 20 μm was mixed with a wax-based adhesive (composed of 55 vol.% paraffin, 25 vol.% polyethylene, 17 vol.% polypropylene and 3 vol.% stearic acid) at a W loading of 60%, 40% and 20%, respectively, and then kneaded at 180° C. for 2 h, cooled naturally, and the cooled material was crushed and sieved to obtain W printing feed;
[0069] Step 2: W green body preparation
[0070] W printing feeds with different loading amounts were added into the 3D printer in descending order, and the printing parameters were printing temperature of 175°C, substrate temperature of 80°C, extrusion amount of 100%, and W green bodies with three layers of loading gradients (60%, 40%, 20%) were printed;
[0071] Step 3: W skeleton preparation
[0072] The W green body prepared in step 2 is subjected to solvent degreasing treatment at 60°C for 36 hours using n-heptane, and then subjected to thermal degreasing treatment in a hydrogen atmosphere at 600°C for 8 hours to obtain a degreased green body, which is pre-sintered at 1500°C for 90 minutes to obtain a W skeleton with a void gradient;
[0073] Step 4: Preparation of W-Cu functional gradient materials
[0074] The W skeleton prepared in step 3 is subjected to a Cu infiltration treatment at 1400° C. for 90 minutes to obtain a W-Cu functional gradient material having W and Cu content varying along the cross section.
[0075] Example 5
[0076] Step 1: W Print Feed Preparation
[0077] W powder with a particle size of 5 μm was mixed with a wax-based adhesive (composed of 55 vol.% paraffin, 25 vol.% polyethylene, 17 vol.% polypropylene and 3 vol.% stearic acid) at a W loading of 50%, 40% and 30%, respectively, and then kneaded at 180° C. for 2 h, cooled naturally, and the cooled material was crushed and sieved to obtain W printing feed;
[0078] Step 2: W green body preparation
[0079] W printing feeds with different loading amounts were added into the 3D printer in descending order, and the printing parameters were printing temperature of 180°C, substrate temperature of 85°C, extrusion amount of 100%, and W green bodies with three layers of loading gradients (50%, 40%, 30%) were printed;
[0080] Step 3: Preparation of W skeleton
[0081] The W green body prepared in step 2 is subjected to solvent degreasing treatment at 20°C for 36 hours using n-heptane, and then subjected to thermal degreasing treatment in a hydrogen atmosphere at 900°C for 6 hours to obtain a degreased green body, which is pre-sintered at 1700°C for 30 minutes to obtain a W skeleton with a void gradient;
[0082] Step 4: Preparation of W-Cu functional gradient materials
[0083] The W skeleton prepared in step 3 is subjected to a Cu infiltration treatment at 1250° C. for 150 min to obtain a W-Cu functional gradient material having W and Cu content varying along the cross section.
[0084] Example 6
[0085] The room temperature thermal conductivity of the materials prepared in Examples 1 to 5 was measured using a laser thermal conductivity meter (LFA-457, NETZSCH, Germany). Before the test, the test samples of each example were cut into cylindrical specimens with a size of φ12.7 mm using wire cutting. After the cutting was completed, the oxide scale on the two end faces and the side of the sintered body was removed using sandpaper, while ensuring that the two end faces were parallel. The room temperature thermal conductivity of the W-Cu functional gradient materials prepared in each example is shown in Table 1.
[0086] The surface microstructure of the W-Cu gradient material samples prepared in Examples 1 to 5 was observed using a field emission scanning electron microscope (model SU8020 Hitachi), and the W and Cu contents on the surface of each sample were determined using EDS. Before the test, the test surface of the sample was ground and polished with 120 mesh, 240 mesh, 400 mesh, 600 mesh, and 800 mesh sandpaper in sequence to obtain a smooth mirror surface before testing the sample.
[0087] Table 1
[0088]
[0089] It can be seen from the above table that the W-Cu functional gradient materials prepared in Examples 1 to 5 have a room temperature thermal conductivity of not less than 219.80 W / (m·K), among which the composition gradient between the layers in the W-Cu functional gradient material prepared in Example 3 is smaller and the interface bonding is better.
[0090] Figure 3 : This is a scanning electron microscope image of the W-Cu functional gradient material prepared according to exemplary embodiment 3 of the present invention. Figure 3 As shown, the black area (Cu) gradually increases along the direction of the arrow, that is, the Cu content gradually increases and the W content gradually decreases along the direction of the arrow, indicating that a W-Cu functional gradient material with a reasonable gradient can be prepared according to the method of an embodiment of the present invention.
[0091] Figure 4 This is the EDS graph of the W-Cu functional gradient material prepared in Example 3 of the present invention. ae are the W and Cu content of different loading layers, respectively. From ae, it can be seen that the W content along the cross section is 75.12wt.%-58.98wt.%, and the Cu content is 24.88wt.%-41.02wt.%. Therefore, the porosity of the W skeleton can be controlled by changing the loading amount, thereby preparing a W-Cu functional gradient material. At the same time, there is no obvious interface stratification in the sample, and the layers are relatively stable.
[0092] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. A method for preparing a W-Cu functional gradient material, characterized in that: The method comprises: Step 1: W Print Feed Preparation W powder and wax-based adhesive were mixed at different loading amounts, kneaded at 180°C for 2h, cooled naturally, and the cooled material was crushed and sieved to obtain W printing feed, wherein the wax-based adhesive consisted of 55vol.% paraffin wax, 25vol.% polyethylene, 17vol.% polypropylene and 3vol.% stearic acid; Step 2: W green body preparation Add W printing feeds with different loading amounts into the 3D printer in order from large to small loading amounts, and print out W green bodies with a loading amount gradient, wherein the W loading amount in the W printing feed is 20-60%, and the loading amount gradient is 2-5 layers; Step 3: Preparation of W skeleton The W green body prepared in step 2 is subjected to solvent degreasing treatment and thermal degreasing treatment to obtain a degreasing green body, and the degreasing green body is pre-sintered to obtain a W skeleton with a pore gradient; Step 4: Preparation of W-Cu functional gradient materials The W skeleton prepared in step 3 is subjected to a Cu infiltration treatment to obtain a W-Cu functional gradient material having W and Cu content varying along the cross section.
2. The method for preparing the W-Cu functional gradient material according to claim 1, characterized in that: In step 1, the particle size of the W powder is 0.2 μm-20 μm.
3. The method for preparing the W-Cu functional gradient material according to claim 1, characterized in that: In step 2, the printing parameters are printing temperature 150-200°C, substrate temperature 70-100°C, and extrusion volume 100-150%.
4. The method for preparing the W-Cu functional gradient material according to claim 1, characterized in that: In step 3, the solvent for solvent degreasing treatment is n-heptane or trichloroethylene, the temperature for solvent degreasing treatment is 20-80° C., and the time for solvent degreasing is 12-36 hours.
5. The method for preparing the W-Cu functional gradient material according to claim 1, characterized in that: In step three, the temperature of the thermal debinding treatment is 500-900° C., the time of the thermal debinding treatment is 6-12 hours, and the environment of the thermal debinding treatment is a hydrogen atmosphere.
6. The method for preparing the W-Cu functional gradient material according to claim 1, characterized in that: In step three, the pre-sintering temperature is 1400-1700° C., and the sintering time is 30-180 min.
7. The method for preparing the W-Cu functional gradient material according to claim 1, characterized in that: In step 4, the temperature of the infiltration of Cu is 1100-1500° C., and the time of the infiltration of Cu is 60-300 min.
8. A W-Cu functional gradient material, characterized in that: The W—Cu functional gradient material is prepared according to any one of the methods described in claims 1-7.
Citation Information
Patent Citations
Method for preparing tungsten-copper continuous gradient material based on SLM technology
CN114734056A
Processing technology for preparing CuW60-CuW90 metal profile part by injection molding
CN112355304A
Method for preparing tungsten / copper functional gradient material by infiltration - weld method
CN1593818A